2008
DOI: 10.1021/jf802146v
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multivariate Analysis to the Effects of Additives on Chemical and Sensory Quality of Stored Coffee Brew

Abstract: The aim of this work was to obtain a black coffee brew to be consumed hot by extension of its shelf-life, by addition of additives. Four pH-regulator agents (sodium and potassium carbonates and bicarbonates), one pH-regulator and antioxidant (sodium citrate), three antioxidants (sodium ascorbate, ethylenediaminetetracetic acid (EDTA), and sodium sulfite), and lactoserum were tested by sensory analysis. Sodium carbonate and bicarbonate were selected for a study of the physico-chemical (soluble and volatile comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
(48 reference statements)
1
28
0
Order By: Relevance
“…A Hypersil-ODS column (5 μm particle size, 250 mm × 4.6 mm) was used. The chromatographic separation was achieved at 25 ºC by using a gradient solvent system with acetonitrile/water adjusted to pH 3.0 with a phosphoric acid solution according to the method described by Perez-Martinez, Sopelana, De Peña, & Cid (2008). The wavelength of detection was 325 nm.…”
Section: -Caffeoylquinic Acid (5-cqa)mentioning
confidence: 99%
See 1 more Smart Citation
“…A Hypersil-ODS column (5 μm particle size, 250 mm × 4.6 mm) was used. The chromatographic separation was achieved at 25 ºC by using a gradient solvent system with acetonitrile/water adjusted to pH 3.0 with a phosphoric acid solution according to the method described by Perez-Martinez, Sopelana, De Peña, & Cid (2008). The wavelength of detection was 325 nm.…”
Section: -Caffeoylquinic Acid (5-cqa)mentioning
confidence: 99%
“…The HPLC analysis was carried out with the same equipment and column described above. The chromatographic separation was achieved at 25 ºC by using a gradient solvent system with acetonitrile/water adjusted to pH 2.5 with a phosphoric acid solution according to the procedure published by Perez-Martinez et al (2008). The wavelengths of detection were 314 nm for caffeic acid, 325 nm for ferulic acid and 210 nm for 4-vinylguaiacol.…”
Section: Hydroxycinnamic Acids (Caffeic Acid and Ferulic Acid) And 4-mentioning
confidence: 99%
“…The selection of the additives and their concentrations were reported in a previous paper (33). pH and Total Solids.…”
Section: Preparation Of Melanoidinsmentioning
confidence: 99%
“…In this type of products, other ingredients or additives, mainly milk derivatives, are usually added to preserve the coffee brew quality, but no studies regarding their influence on the antioxidant capacity have been found. In a previous work carried out by our research group, the addition of sodium carbonate or sodium bicarbonate, as pH-regulator agents, to black coffee brews has been proposed to extend the shelf life (33).…”
Section: Influence Of the Addition Of Acidity Correctors To Coffee Brewmentioning
confidence: 99%
See 1 more Smart Citation